A review of the effects of the anesthetic gas nitrous oxide on the immune system; a starting point for future experiences. (3rd May 2020) - Mohsenzadegan, Monireh; Kourosh arami, Masoumeh; Oshaghi, Mojgan; Sedigh Maroufi, Shahnam
Abstract: Nitrous oxide is a common gas used as an anesthetic agent and analgesic medication in operating rooms. The gas inhibits vitamin B12 dependent-methionine synthase, which converts L-homocysteine and 5-methyltetrahydrofolate to L-methionine and tetrahydrofolate, respectively, via a methylation process. The immune system has been frequently reported to be suppressed in anesthetized subjects during the postoperative period. Although previous reviews have focused on the pathophysiologic role of nitrous oxide, none of them has considered the harmful effects of nitrous oxide on the Defense system of the host. In this article, the authors review current studies on the effects of nitrous oxide on the immune system of both patients undergoing surgery and occupational exposure, as well as preclinical studies. Moreover, this paper opens a new horizon for future studies in the context of underlying mechanisms of nitrous oxide actions on the immune system.